Technical Investigation of Photocatalytic Coatings on Coastal Urban Road Pavements for Stormwater Runoff Pollution Control - Nguyễn, Phan Anh; Bùi, Ngọc Dung (Journal of Transportation Science and Technology, 2026)
Stormwater runoff from coastal urban roads is an important non-point pollution source. This study evaluates the potential of TiO₂ photocatalytic coatings for stormwater pollution mitigation along Vo Nguyen Giap Road in Hai Phong. An integrated framework combining runoff hydrology and pollutant load analysis was developed to quantify the environmental benefits of this approach. Using the Rational method and event mean concentrations, pollutant loads before and after treatment were estimated for average annual conditions and an extreme rainfall event on 9 June 2024 (200 mm) combined with tidal influence. Results indicate reductions of about 50% for COD, 40% for nitrogen, and 60% for phosphorus, while heavy metals decrease by around 20%. The results suggest that TiO₂ coatings could be integrated into coastal urban pavement maintenance, although durability and traffic safety require further investigation